Production of banana cake premix from banana (Musa acuminata Colla) by-products via foam mat drying process - Marzlan, Anis Asyila; Muhialdin, Belal J.; Meor Hussin, Anis Shobirin (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Banana is a perishable fruit and rapidly overripe which can cause food waste problems to occur if not used to prepare other foods. Drying would be useful to overcome this problem by converting the overripe banana into a value-added product. Therefore, this study aims to evaluate the effect of different temperatures for foam mat drying on overripe banana puree. Besides, the sensory attributes and acceptability of banana cakes produced will be evaluated. Methods: The overripe banana puree was subjected to foam mat drying and the dried powder was subjected to banana cake production. Physical analysis, chemical analysis, and sensory evaluation were carried out for the banana cakes. Results: A significant different (p≥0.05) was observed for all of the overripe banana powder. The sensory evaluation showed that banana cake prepared from overripe banana powder and added with banana essence in the cake batter had significant difference (p<0.05) for the attributes of aroma, appearances, flavour, and after taste. In contrast, all the banana cakes samples showed no significant difference (p≥0.05) for the attribute of texture. Conclusion: This study showed that overripe banana powder has the potential to produce banana cake premix.